2013
DOI: 10.1186/1471-2334-13-51
|View full text |Cite
|
Sign up to set email alerts
|

Heparin binding protein in patients with acute respiratory failure treated with granulocyte colony-stimulating factor (filgrastim) – a prospective, placebo-controlled, double-blind study

Abstract: BackgroundHeparin Binding Protein (HBP) is released to blood circulation from activated neutrophils in bacterial infections. It is a potential inducer of vascular leakage and precludes the development of septic shock. Filgrastim induces the production of new neutrophils and modulates their bacterial-killing activity. We evaluated the effect of filgrastim on HBP –concentrations in critically ill patients with acute respiratory failure.Methods59 critically ill patients with acute respiratory failure were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Administration of products that may activate neutrophils could potentially increase HBP plasma levels. One study demonstrated a small but significant increase in plasma HBP concentration after administration of granulocyte colony‐stimulating factor (filgrastim) compared to controls but failed to show any differences in clinical effect .…”
Section: Hbp In Noninfectious Critical Illnessmentioning
confidence: 99%
“…Administration of products that may activate neutrophils could potentially increase HBP plasma levels. One study demonstrated a small but significant increase in plasma HBP concentration after administration of granulocyte colony‐stimulating factor (filgrastim) compared to controls but failed to show any differences in clinical effect .…”
Section: Hbp In Noninfectious Critical Illnessmentioning
confidence: 99%